Prevalence of acute otitis media in a tertiary care center of Assam - Mili MK,; Sharmistha Talukdar,; Monikuntal Sarmah,; Saikia, Asha (Asian Journal of Medical Sciences, 2023)
Background: Otitis media is infection of the middle ear cleft, which comprises acute and chronic otitis media and otitis media with effusion. Acute otitis media (AOM) is the second most prevalent pediatric emergency. Aims and Objectives: The aim of the study was to assess the epidemiology and clinical manifestations of AOM cases reported to the ENT OPD. Materials and Methods: A retrospective study was conducted in a tertiary care center of Assam from January 2021 to December 2022. A total of 840 patients from a wide range of socioeconomic strata were included in the study who belong to Upper Assam, parts of Arunachal Pradesh and Nagaland region. Results: Majority (25.8%) of the patients were below the age of 10 years. The age group of 31–40 years (25.2%) was next in line. In the age range of 71–80 years, the least number of patients (0.3%) were observed. The majority (53.09%) of the patients were from Dibrugarh district of Assam. Conclusion: This study has brought to light the prevalence of AOM in this region and the need for the health department to raise public understanding of the significance of a healthy lifestyle in the prevention of AOM, early diagnosis, and treatment.